Cold atmospheric plasma-enabled platelet vesicle incorporated iron oxide nano-propellers for thrombolysis - Jheng, Pei-Ru; Chiang, Chia-Che; Kang, Jiunn-Horng; Fan, Yu-Jui; Wu, Kevin C-W; Chen, Yan-Ting; Liang, Jia-Wei; Bolouki, Nima; Lee, Jyh-Wei; Hsieh, Jang-Hsing; Chuang, Er-Yuan (Materials today. Bio, 2023)
A new approach to treating vascular blockages has been developed to overcome the limitations of current thrombolytic therapies. This approach involves biosafety and multimodal plasma-derived theranostic platelet vesicle incorporating iron oxide constructed nano-propellers platformed technology that possesses fluorescent and magnetic features and manifold thrombus targeting modes. The platform is capable of being guided and visualized remotely to specifically target thrombi, and it can be activated using near-infrared phototherapy along with an actuated magnet for magnetotherapy. In a murine model of thrombus lesion, this proposed multimodal approach showed an approximately 80 % reduction in thrombus residues. Moreover, the new strategy not only improves thrombolysis but also boosts the rate of lysis, making it a promising candidate for time-sensitive thrombolytic therapy.
Keywords: Phototherapy; Platelet vesicle; Magnetotherapy; Cold atmospheric plasma; Iron oxide; Thrombolysis